2020
DOI: 10.1002/ps.6076
|View full text |Cite
|
Sign up to set email alerts
|

Review: Allelochemicals as multi‐kingdom plant defence compounds: towards an integrated approach

Abstract: The capability of synthetic pesticides to manage weeds, insect pests and pathogens in crops has diminished due to evolved resistance. Sustainable management is thus becoming more challenging. Novel solutions are needed and, given the ubiquity of biologically active secondary metabolites in nature, such compounds require further exploration as leads for novel crop protection chemistry. Despite improving understanding of allelochemicals, particularly in terms of their potential for use in weed control, their int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 100 publications
(233 reference statements)
1
31
0
1
Order By: Relevance
“…The latter could be due to traits that allow the plants to quickly take up available resources, resulting in high intrinsic growth rates (Dawson et al 2011;Zhang and van Kleunen 2019). It has also been suggested that the high competitive ability of some invasive plants could be achieved by suppression of germination and growth of neighboring plants by allelochemicals (Baker 1974;Callaway and Aschehoug 2000;Hickman et al 2020). In support of this idea, Kalisz et al (2021) showed that of the 524 invasive plant species in their database, at least half have known allelopathic effects.…”
Section: Introductionmentioning
confidence: 94%
“…The latter could be due to traits that allow the plants to quickly take up available resources, resulting in high intrinsic growth rates (Dawson et al 2011;Zhang and van Kleunen 2019). It has also been suggested that the high competitive ability of some invasive plants could be achieved by suppression of germination and growth of neighboring plants by allelochemicals (Baker 1974;Callaway and Aschehoug 2000;Hickman et al 2020). In support of this idea, Kalisz et al (2021) showed that of the 524 invasive plant species in their database, at least half have known allelopathic effects.…”
Section: Introductionmentioning
confidence: 94%
“…2 Faculty of Science, RECETOX, Masaryk University, Brno, Czech Republic. 3 Environmental Analytics, Agroscope, Switzerland.…”
Section: Availability Of Data and Materialsmentioning
confidence: 99%
“…Some show low acute toxicity like the glycoalkaloids in potato or isoflavones in clover, medium toxicity as linamarin in cassava and coniin in poisonous hemlock, while some are very toxic like ricin in castor beans and the cyanotoxin saxitoxin produced by blue-green algae (Table 1). Many of these compounds may have or have had a function as natural defense chemicals in order for the toxin producing organism to compete with other species, and to protect itself against herbivoric and pathogenic attacks and other stressors [3,4].…”
mentioning
confidence: 99%
“…The potential effects of an imminent ban of glyphosate in Mexico are discussed in a perspective 55 . The potential use of allelochemicals in integrated weed management is reviewed 56 …”
Section: Figurementioning
confidence: 99%